Injury profile in women`s football: A systematic review and meta-analysis - López-Valenciano, A.; Raya-González, J.; Garcia-Gómez, J. A.; Aparicio-Sarmiento, A.; Sainz de Baranda, P.; De Ste Croix, M.; Ayala, F. (Sports Medicine, 2021)
Background: Football is the most popular sport among women; however, little is known about the injury profile in this population. This information would help design tailored injury risk mitigation strategies that may make football safer for women.